TRAUMATIC CERVICAL SPINAL CORD INJURY. IS URGENT INTERVENTION SUPERIOR TO DELAYED INTERVENTION? A META-ANALYSIS EVALUATION - I Ketut Martiana; Donny Permana; Lukas Widhiyanto (Journal Orthopaedi and Traumatology Surabaya)
Introduction: Cervical spine is the most mobile part of the human spine, thus making it the most vulnerable compared to all the other vertebral structures. Surgical procedures are usually performed within the first 24 hours, or 4-6 weeks after trauma in order to prevent any secondary trauma. The research was conducted to evaluate the amount of time of the surgical procedure towards the effectivity and improvement of the neurological status in the cervical injury or acute spinal cord injury (ASCI). Methods: A meta-analysis research which evaluate the effectivity of surgical procedure on cervical trauma/ASCI, with the database procured from PubMed, Embase, and Cochrane. The main parameter is the decompression procedure and the clinical outcome which were categorized. The time of surgery or decompression are categorized into "<24 hours” and ">24 hours”, the neurological outcome is categorized into "improvement” and "no improvement”. The data was presented in odd ratio (OR) and confidence interval (CI) and were further analyzed by forest plot.